A Descriptive Study of Clinical Profile of Fever with Thrombocytopenia at Tertiary Care Centre of Maharashtra (GAIMS Journal of Medical Sciences, 2026)
Introduction: Fever is a pervasive and ubiquitous theme in human myth, art and science. Fever is such a common manifestation of illness that it is not surprising to find accurate descriptions of the febrile patients in early-recorded history. A fever rarely comes without other symptoms and sign. It is often accompanied by specific complaints or pattern. Many times, it is associated with low platelet count. The normal platelet count is 150000-450000/ μL. Thrombocytopenia is defined as platelet count less than 150000/ μL.Material and Methods: The present study was prospective observational study conducted on patients, who were admitted at tertiary care hospital in urban setting during Feb 2013 to July 2014. This study conducted at Government medical college and Hospital, Latur. Sample size was 200.Results: The present study, conducted on 200 patients with fever and thrombocytopenia, revealed that the majority of cases occurred in young adults, with 57% belonging to the 15–30 years’ age group and a male predominance (M: F = 2.12:1). Dengue fever (40%) emerged as the leading cause, followed by malaria (33%), while septicemia (8%) was the most common contributor to mortality. Most patients presented with platelet counts less than 50,000/cumm showed bleeding manifestations 34% of cases, predominantly petechiae and purpura (70%). The overall recovery rate was good (96%), with mortality observed in 4% of cases, largely due to septicemia and severe thrombocytopenia (< 20,000/cumm).Conclusion: These findings emphasize that fever with thrombocytopenia is a significant clinical presentation in hospitals, requiring careful evaluation to differentiate between infectious etiologies.